2006
DOI: 10.1001/jama.295.7.761
|View full text |Cite|
|
Sign up to set email alerts
|

Effect of Rimonabant, a Cannabinoid-1 Receptor Blocker, on Weight and Cardiometabolic Risk Factors in Overweight or Obese Patients

Abstract: In this multicenter trial, treatment with 20 mg/d of rimonabant plus diet for 2 years promoted modest but sustained reductions in weight and waist circumference and favorable changes in cardiometabolic risk factors. However, the trial was limited by a high drop-out rate and longer-term effects of the drug require further study. Clinical Trials Registration ClinicalTrials.gov Identifier: NCT00029861.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

44
875
1
36

Year Published

2007
2007
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 1,156 publications
(964 citation statements)
references
References 29 publications
44
875
1
36
Order By: Relevance
“…In four placebo-controlled, multinational, double-blind, clinical RIO (Rimonabant In Obesity) studies, rimonabant has been shown not only to reduce body weight, but additionally to improve cardiometabolic risk factors, such as waist circumference, HbA1c, high-density lipoprotein and triglyceride in overweight/obese patients. [12][13][14][15] The antiobese effect of rimonabant is ascribed to its CB1 receptor antagonism in the hypothalamus 16,17 and nucleus accumbens, [18][19][20] resulting in reduced food intake predominantly of palatable food. In addition to the central effects on food intake and body weight, the improvement in the cardiometabolic risk factors, which have been shown to be beyond that what would be expected by body weight reduction alone, is hypothesized to involve also peripheral CB1 receptor antagonism.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In four placebo-controlled, multinational, double-blind, clinical RIO (Rimonabant In Obesity) studies, rimonabant has been shown not only to reduce body weight, but additionally to improve cardiometabolic risk factors, such as waist circumference, HbA1c, high-density lipoprotein and triglyceride in overweight/obese patients. [12][13][14][15] The antiobese effect of rimonabant is ascribed to its CB1 receptor antagonism in the hypothalamus 16,17 and nucleus accumbens, [18][19][20] resulting in reduced food intake predominantly of palatable food. In addition to the central effects on food intake and body weight, the improvement in the cardiometabolic risk factors, which have been shown to be beyond that what would be expected by body weight reduction alone, is hypothesized to involve also peripheral CB1 receptor antagonism.…”
Section: Introductionmentioning
confidence: 99%
“…In addition to the central effects on food intake and body weight, the improvement in the cardiometabolic risk factors, which have been shown to be beyond that what would be expected by body weight reduction alone, is hypothesized to involve also peripheral CB1 receptor antagonism. [12][13][14][15] There are convincing results reported on the sustained body weight reduction in spite of the transient effects on food reduction in diet-induced obese mice, as well as in genetic rat models of obesity, such as the fa/fa Zucker rat. [21][22][23][24][25] The transience of reduced food intake in the presence of persistent reduction of body weight caused by rimonabant in rodent models has recently been elucidated to be caused by increased energy expenditure based on increased fat oxidation measured by indirect calorimetry, which contributed more to the sustained body weight reducing effect of rimonabant than reduced food intake.…”
Section: Introductionmentioning
confidence: 99%
“…In this context, it is also worthwhile to note that the most frequently encountered side effects during the recently conducted phase-III trials of the CB1 receptor antagonist rimonabant (SR141716) as an anti-obesity treatment included anxiety and mood disturbances. [29][30][31] Studies on the function of endocannabinoids in classic animal models of depression or antidepressant-like behavior, however, have so far been sparse and revealed contradictory results in rats and mice. The forced swim test (FST) represents one of the most widely used tests to detect antidepressant-like activities of drugs as well as depressionlike behavior in genetically engineered mice.…”
Section: Introductionmentioning
confidence: 99%
“…This retention programme was implemented proactively and was successful at improving upon the reported 53% 1‐year retention rate in the Rio‐North American study, which studied a similar weight loss drug in patients with similar BMI but without diabetes in the USA and Canada, also over a 1‐year time period 1, 19, and even improved upon the retention rate of Phase 3 trials conducted with more recently approved weight loss agents 2, 3, 4, 5.…”
Section: Discussionmentioning
confidence: 99%
“…On average, one‐third to one‐half of participants drops out of these large trials by 1 year 1, 2, 3, 4, 5. Such high‐attrition rates result in missing data that limit the interpretation and generalizability of findings 6.…”
Section: Introductionmentioning
confidence: 99%